Plate-uncovering self-compacting concrete as well as preparation method and application thereof

By using specific coagulation agents, polymer emulsions and nanomaterials in the self-compression concrete of the uncovered self-finished concrete, the problems of high water leakage and reduced strength are solved, and efficient concrete modification is achieved, and performance requirements of relevant standards are met.

CN119822774AActive Publication Date: 2025-04-15FUJIAN KZJ NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411986074.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing self-filled concrete with unloaded plates has the problem of high water excretion after using ordinary polycarboxylic acid water reducing agent, and the recycled glass material replaces the blending material to reduce strength, high water excretion rate and long settling time.

Method used

Specific types and contents of coagulation agents, polyether modified silicone oils, polymer emulsions, beautifiers, and are combined with gas-phase nano-silica toughened high-strength micropowders, modified sulfonated phenolic resins and viscosity modifiers. Through the coordinated cooperation of each component, the fluidity and coagulation properties of the self-condensed concrete of the modified self-contained concrete are used.

Benefits of technology

It effectively solves the problem of high water secretion rate when used in polycarboxylic acid water reducing agent. At the same time, in addition to retaining the advantages of recycled glass materials (high transparency and strong scratch resistance), the strength of concrete is improved, the water secretion rate is reduced, and the setting time is extended, so that the self-condensed concrete of the obtained peeled-plate complies with the provisions of relevant standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222608930000251
    Figure BDA0005222608930000251
  • Figure BDA0005222608930000261
    Figure BDA0005222608930000261
Patent Text Reader

Abstract

The invention belongs to the field of constructional engineering materials, and relates to uncovering self-compacting concrete as well as a preparation method and application thereof. The uncovering self-compacting concrete comprises a liquid material and a dry material; the liquid material contains a water reducing agent, a slump retaining agent, a thickening time control agent, a defoaming agent, a polymer emulsion, a beautifying agent, a viscosity reducer, water, and optional air entraining agent, stabilizer and preservative; the dry material contains glass powder, glass sand, cement, broken stone, gypsum, an expanding agent, gas-phase nano silicon dioxide toughened high-strength micro powder, modified sulfonated phenolic resin and a viscosity modifier. According to the uncovering self-compacting concrete disclosed by the invention, the problem of high bleeding rate caused when a polycarboxylic acid water reducer and a slump retaining agent are applied to production of the uncovering self-compacting concrete can be perfectly solved through synergistic cooperation of all the components, and meanwhile, the advantages of high transparency and strong scratch resistance caused by replacement of an admixture with a regenerated glass material are reserved; the strength of the uncovering self-compacting concrete is effectively reduced, the bleeding rate is reduced, and the setting time is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building engineering materials, and in particular relates to a self-compacting concrete with a peeling plate, a preparation method and an application thereof. Background Art

[0002] Self-compacting concrete refers to concrete that can flow and compact under its own gravity, completely fill the formwork even in the presence of dense steel bars, and has good homogeneity and does not require additional vibration. As early as the early 1970s, Europe had already begun to use lightly vibrated concrete, but SCC was not developed in Japan until the late 1980s. The main reason for Japan to develop SCC was to solve the contradiction between the reduction of skilled workers and the improvement of the durability of concrete structures. Self-compacting concrete was first used in civil engineering projects in Sweden's transportation network in Europe in the mid-1990s. Subsequently, the European Community established a multinational cooperative self-compacting concrete guidance project. Since then, the application of self-compacting concrete has generally increased throughout Europe. The most prominent feature of self-compacting concrete is that the mixture has good working performance. Even under conditions of dense reinforcement and complex shapes or conditions where casting is difficult and vibration is difficult, it can be uniformly and densely filled and formed by relying solely on its own weight without vibration, which brings great convenience to construction operations. At the same time, it has technical and economic effects such as improving the construction environment, accelerating the construction progress, increasing labor productivity, and reducing project costs. It is known as "the most revolutionary development in concrete technology in recent decades."

[0003] With the continuous development of related technologies, various types of self-compacting concrete have gradually emerged and have been successfully applied to large-scale projects such as housing construction, water conservancy, bridges, tunnels and railways. Among them, the high-speed railway CRTSⅢ type ballastless track self-compacting concrete, as the most technically difficult type of self-compacting concrete, has been determined to be used in the construction of multiple projects. The design strength grade of this self-compacting concrete project requires C40, which should have extremely low viscosity, good fluidity and workability, and the demolding appearance should be flat and clean, with consistent color, and no obvious bubbles and water marks. However, the concrete mix ratio has the characteristics of low water-cement ratio, high sand ratio, and large amount of cementitious materials. The use of ordinary polycarboxylic acid high-performance water reducer often leads to slow dispersion, water seepage, slurry, poor workability, high viscosity and many bubbles, which cannot meet the construction requirements and seriously affect the project construction progress.

[0004] As for the existing publicly available formula of self-compacting concrete products, its components can be roughly divided into six categories, namely, cementitious materials, mineral aggregates, setting regulators, waterproofing agents, rheological agents and modified components. Among them, ordinary Portland cement, sulphoaluminate cement, high alumina cement or white cement can be selected as the cementitious materials of the self-compacting concrete according to different functions to give the self-compacting concrete superior compressive, flexural and bonding strengths. At the same time, the particle grading of the self-compacting concrete requires the use of coarser fillers (such as machine-made sand and river sand) and finer admixtures (such as ground calcium carbonate powder) to achieve the best compactness effect. Early strength agents and accelerators can also be added to the self-compacting concrete to improve the early cement setting strength, and retarders can be used to slow down the gypsum setting rate to extend the operable time of the self-compacting concrete. When the redispersible rubber powder and emulsion act on the self-compacting concrete, the self-compacting concrete can be modified to form a strong polymer film, thereby improving the fluidity, tensile strength and flexural strength of the self-compacting concrete, and can also reduce the elastic modulus and reduce the internal stress of the self-compacting concrete system.

[0005] The raw materials of self-compacting concrete are abundant. Aggregates such as machine-made sand, river sand, quartz sand, stone powder and ceramic powder can all be used to prepare self-compacting concrete, among which machine-made sand is the most common. At the same time, with the enrichment of various raw material sources and the in-depth research on related formulation technologies, recycled glass materials are gradually becoming an emerging research direction for self-compacting concrete products with their stable acid and alkali resistance, chemical inertness and low expansion coefficient. Recycled glass materials have small particle size, good dispersibility, high transparency, good anti-settling effect, good affinity and strong steric hindrance. They can be easily dispersed in the self-compacting concrete system. After film formation, they can increase the fullness of the self-compacting concrete, maintain clear transparency, and provide good scratch resistance. However, the application of recycled glass materials in self-compacting concrete has problems such as low strength, high water seepage rate and long setting time. The reason is that although the recycled glass material has a good grading, its surface morphology is relatively smooth and its reaction activity with cement is lower than that of admixtures such as fly ash and mineral powder. As a result, the bonding ability of the cementitious material and the aggregate is weakened, and the time required for the cement particles in the self-compacting concrete system to connect with each other to form a skeleton structure is prolonged. Summary of the invention

[0006] The first purpose of the present invention is to provide a new self-compacting concrete with a peeling plate to solve the problem of high water seepage in the self-compacting concrete with a peeling plate after using ordinary polycarboxylic acid water-reducing agent, and to make up for the defects of reduced concrete strength, high water seepage rate and long setting time caused by using recycled glass materials instead of admixtures.

[0007] The second object of the present invention is to provide a method for preparing the above-mentioned self-compacting concrete.

[0008] The third object of the present invention is to provide the application of the above-mentioned self-compacting concrete in the field of construction.

[0009] Specifically, the self-compacting concrete provided by the present invention comprises a liquid material and a dry material; the liquid material contains 170-180 parts by weight of a water reducer, 40-90 parts by weight of a slump retaining agent, 40-60 parts by weight of a setting regulator, 0.1-2 parts by weight of a defoamer, 10-30 parts by weight of a polymer emulsion, 10-40 parts by weight of a beautifying agent, 20-40 parts by weight of a viscosity reducer, 500-650 parts by weight of water, and 0-10 parts by weight of an optional air entraining agent, 0-10 parts by weight of a stabilizer, and 0-10 parts by weight of a preservative; the setting regulator is selected from calcium nitrate, triisopropanolamine, sodium fluoride, potassium fluoride, sodium formate, potassium formate, citric acid, hexametazoline, and the like. At least one of sodium phosphate, potassium hexametaphosphate, sodium gluconate, potassium gluconate and maltodextrin, the defoamer is polyether modified silicone oil, and the polymer emulsion is silicone modified styrene and acrylate copolymer emulsion; the dry material contains 50-130 weight parts of glass powder, 600-700 weight parts of glass sand, 350-400 weight parts of cement, 800-900 weight parts of crushed stone, 50-80 weight parts of gypsum, 30-50 weight parts of expansion agent, 70-100 weight parts of gas-phase nano-silica toughened high-strength micropowder, 30-50 weight parts of modified sulfonated phenolic resin and 30-40 weight parts of viscosity modifier.

[0010] The preparation method of the self-compacting concrete with a slab opening provided by the invention comprises the steps of evenly mixing the components of a liquid material to obtain a liquid material; and evenly mixing the components of a dry material to obtain a dry material.

[0011] The invention uses recycled glass materials (glass powder / glass sand) to replace admixtures, adopts specific types and contents of setting regulators, polyether modified silicone oil and polymer emulsion, beautifier, adhesive and optional air entraining agent, stabilizer and preservative to modify the self-compacting concrete for peeling boards, and simultaneously uses specific contents of gas-phase nano-silica toughening high-strength micropowder, modified sulfonated phenolic resin and viscosity modifier. Through the coordinated cooperation of various components, the problem of high water bleeding rate caused by the application of polycarboxylic acid water reducer and slump retainer in the production of self-compacting concrete for peeling boards can be perfectly solved. At the same time, the advantages of high transparency and strong scratch resistance brought by the replacement of admixtures by recycled glass materials are retained, and the strength reduction of the self-compacting concrete for peeling boards is effectively improved, the water bleeding rate is reduced and the setting time is prolonged, so that the obtained self-compacting concrete for peeling boards meets T / CECS203 "Technical Specifications for Application of Self-Compacting Concrete", QC / R 596 "Self-compacting concrete for CRTS III slab track of high-speed railway", TB / T3275 "Railway concrete", GB 8076 "Concrete admixtures", JGJ / T 283 "Technical specification for application of self-compacting concrete" and T / CCES 02 "Guide to design and construction of self-compacting concrete" and other relevant standards. DETAILED DESCRIPTION

[0012] The self-compacting concrete provided by the present invention comprises liquid material and dry material. The mass ratio of the liquid material to the dry material is preferably (0.3-3):(100-500), such as 0.3:100, 0.5:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 0.3:200, 0.5:200, 1:200, 1.5:200, 2:200, 2.5:200, 3:200, 0.3:300, 0.5 :300, 1:300, 1.5:300, 2:300, 2.5:300, 3:300, 0.3:400, 0.5:400, 1:400, 1.5:400, 2:400, 2.5:400, 3:400, 0.3:500, 0.5:500, 1:500, 1.5:500, 2:500, 2.5:500, 3:500 or any value therebetween. In addition, the self-compacting concrete for uncovering the board generally also contains added water. The mass ratio of the liquid material to the added water is preferably (0.3-3):(10-20), such as 0.3:10, 0.5:10, 1:10, 1.5:10, 2:10, 2.5:10, 3:10, 0.3:15, 0.5:15, 1:15, 1.5:15, 2:15, 2.5:15, 3:15, 0.3:20, 0.5:20, 1:20, 1.5:20, 2:20, 2.5:20, 3:20 or any value therebetween. The self-compacting concrete has good working performance in an environment of 0-50°C, and is environmentally friendly and pollution-free.

[0013] In the present invention, the liquid material contains a water reducing agent, a slump retaining agent, a setting regulator, a defoaming agent, a polymer emulsion, a beautifying agent, a viscosity reducing agent and water, as well as an optional air entraining agent, a stabilizer and a preservative. The content of the water reducing agent is 170 to 180 parts by weight, such as 170, 172, 175, 178, 180 parts by weight or any value therebetween; the content of the slump retaining agent is 40 to 90 parts by weight, such as 40, 50, 60, 70, 80, 90 parts by weight or any value therebetween; the content of the setting regulator is 40 to 60 parts by weight, such as 40, 45, 50, 55, 60 parts by weight or any value therebetween; the content of the defoaming agent is The content of the polymer emulsion is 10-30 parts by weight, such as 10, 15, 20, 25, 30 parts by weight or any value therebetween; the content of the beautifying agent is 10-40 parts by weight, such as 10, 15, 20, 25, 30, 35, 40 parts by weight or any value therebetween. any value between; the content of the viscosity reducer is 20 to 40 parts by weight, such as 20, 25, 30, 35, 40 parts by weight or any value therebetween; the amount of water is 500 to 650 parts by weight, such as 500, 520, 540, 560, 580, 600, 620, 650 parts by weight or any value therebetween; the content of the air entraining agent is 0 to 10 parts by weight, such as 0, 0.1, 0.2, 0.4, 0.6, 0.8, 1, 2, 4, 6, 8, 10 parts by weight or any value therebetween; the content of the stabilizer is 0 to 10 parts by weight, such as 0, 0.1, 0.2, 0.4, 0.6, 0.8, 1, 2, 4, 6, 8, 10 parts by weight or any value therebetween; the content of the preservative is 0 to 10 parts by weight, such as 0, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 6, 7, 8, 9, 10 parts by weight or any value therebetween.

[0014] In the present invention, the dry material contains glass powder, glass sand, cement, crushed stone, gypsum, expansion agent, gas-phase nano-silicon dioxide toughening high-strength micropowder, modified sulfonated phenolic resin and viscosity modifier. The content of the glass powder is 50-130 parts by weight, such as 50, 60, 70, 80, 90, 100, 110, 120, 130 parts by weight or any value therebetween; the content of the glass sand is 600-700 parts by weight, such as 600, 620, 640, 660, 680, 700 parts by weight or any value therebetween; the content of the cement is 350-400 parts by weight, such as 350, 360, 370, 380, 390, 400 parts by weight or any value therebetween; the content of the crushed stone is 800-900 parts by weight, such as 800, 820, 840, 860, 880, 900 parts by weight or any value therebetween; the content of the gypsum is 50- 80 parts by weight, such as 50, 60, 70, 80 parts by weight or any value therebetween; the content of the expander is 30-50 parts by weight, such as 30, 35, 40, 45, 50 parts by weight or any value therebetween; the content of the fumed nano-silica toughened high-strength micropowder is 70-100 parts by weight, such as 70, 75, 80, 85, 90, 95, 100 parts by weight or any value therebetween; the content of the modified sulfonated phenolic resin is 30-50 parts by weight, such as 30, 35, 40, 45, 50 parts by weight or any value therebetween; the content of the viscosity modifier is 30-40 parts by weight, such as 30, 32, 34, 36, 38, 40 parts by weight or any value therebetween.

[0015] In the present invention, the water reducer is preferably a short main chain long side chain polycarboxylic acid grafted multipolymer. The slump retainer is preferably a long main chain short side chain polycarboxylic acid grafted multipolymer. The main function of the water reducer and slump retainer is to adsorb on the surface of cement particles. The particles repel each other due to the same charge, so that the cement particles are dispersed and the excess water between the particles is released to produce a water-reducing effect. The water reducer and slump retainer can form an adsorption film on the surface of cement particles, thereby delaying the hydration process of cement, making the growth of cement stone crystals more perfect, reducing the capillary voids caused by water evaporation, and improving the strength, hardness and structural density of concrete.

[0016] In the present invention, the setting regulator is used to adjust the setting time of the self-compacting concrete, prevent the concrete from setting quickly or slowly, and improve the strength of the concrete through alkali excitation. The setting regulator is selected from at least one of calcium nitrate, triisopropanolamine, sodium fluoride, potassium fluoride, sodium formate, potassium formate, citric acid, sodium hexametaphosphate, potassium hexametaphosphate, sodium gluconate, potassium gluconate and maltodextrin.

[0017] In the present invention, the main function of the defoamer is to destroy the elastic membrane of harmful bubbles in concrete and inhibit the generation of harmful bubbles; if harmful bubbles have already been generated, the defoamer particles will immediately capture the hydrophobic chain ends on the foam surface after contacting the foam, and then quickly spread to form a very thin double membrane layer, further diffuse and invade in layers, replace the membrane wall of the original foam, and destroy the mechanical balance of the oriented membrane under the strong traction of the surrounding membrane layer with large surface tension, thereby achieving the effect of breaking and inhibiting bubbles, thereby improving the strength of concrete. The defoamer is preferably a polyether modified silicone oil.

[0018] In the present invention, the polymer emulsion is a copolymer emulsion of silicone-modified styrene and acrylate. The copolymer emulsion of silicone-modified styrene and acrylate is preferably a ternary copolymer emulsion of silicone-styrene-acrylate. In a preferred embodiment, the ternary copolymer emulsion of silicone-styrene-acrylate is prepared by emulsion polymerization of unsaturated silicone monomers, styrene monomers and acrylic acid / ester monomers. The method of the emulsion polymerization reaction preferably includes dissolving the composite emulsifier I, acrylic acid / ester monomers and styrene monomers in water to obtain a pre-emulsion; dissolving the initiator in water to obtain an initiator solution; dissolving bicarbonate and composite emulsifier II in water and heating to 50°C to 70°C, adding part of the pre-emulsion and part of the initiator solution, and then heating to 75°C to 80°C for heat preservation and reaction until the liquid turns blue; dissolving the unsaturated silicone monomer in the remaining pre-emulsion, dripping the remaining initiator solution, and heat preservation and reaction after dripping. After the reaction is completed, the temperature is lowered to below 40°C and the pH value is adjusted to 7 to 8 and then filtered to obtain a ternary copolymer emulsion of silicone-styrene-acrylate. The molar ratio of the unsaturated silicone monomer, styrene monomer and acrylic acid / ester monomer is preferably (1 to 6): (1 to 10): (1 to 10). The unsaturated silicone monomer can be vinyl trimethoxysilane and / or vinyl triethoxysilane. The styrene monomer can be styrene and / or methyl styrene. The acrylic acid / ester monomer can be selected from at least one of acrylic acid, methacrylic acid, methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate and butyl methacrylate. The emulsifier used in the emulsion polymerization reaction is preferably a composite emulsifier obtained by compounding nonylphenol polyoxyethylene ether and sodium dodecyl sulfate in a mass ratio of (2-5):1.

[0019] In the present invention, the beautifying agent is preferably a grafted multipolymer of dodecanol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride. In a preferred embodiment, the beautifying agent is prepared according to the following method: polyoxyethylene sorbitan monooleate, dodecanol, and dodecenyl succinic anhydride are subjected to graft copolymerization reaction under the action of concentrated sulfuric acid and organic amine to obtain a grafted multipolymer of dodecanol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride. When the grafted multipolymer of dodecanol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride is used as a beautifying agent in concrete, the electronic potential energy distribution between cement particles can be adjusted, and the surface activity of cement molecules can be reduced. At the same time, due to its high activity, it can replace water reducers and slump retainers to be preferentially adsorbed by flocculant molecules, effectively improving the plasticization and dispersion of liquid materials, reducing the water exudation and viscosity of concrete, and improving the workability and working performance of concrete. Among them, the mass ratio of polyoxyethylene sorbitan monooleate, dodecanol, dodecenyl succinic anhydride, concentrated sulfuric acid and organic amine is preferably 100:(15-50):(3-30):(1-10):(3-15). Based on 100 parts by weight of polyoxyethylene sorbitan monooleate, the amount of dodecanol is preferably 15 to 50 parts by weight, such as 15, 20, 25, 30, 35, 40, 45, 50 parts by weight or any value therebetween; the content of dodecenyl succinic anhydride is preferably 3 to 30 parts by weight, such as 3, 5, 10, 15, 20, 25, 30 parts by weight or any value therebetween; the content of concentrated sulfuric acid is preferably 1 to 10 parts by weight, such as 1, 2, 4, 6, 8, 10 parts by weight or any value therebetween; the content of the organic amine is 3 to 15 parts by weight, such as 3, 5, 8, 10, 12, 15 parts by weight or any value therebetween. The conditions for the graft copolymerization reaction preferably include a temperature of 50°C to 90°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or any value therebetween; a pH of 2 to 6, such as 2, 3, 4, 5 or 6; and a time of 6h to 8h, such as 6h, 6.5h, 7h, 7.5h, 8h or any value therebetween.

[0020] In the present invention, the viscosity reducer is preferably an alcohol-ester-ether-phosphoric acid-amide multi-polymer derivative. In a preferred embodiment, the alcohol-ester-ether-phosphoric acid-amide multi-polymer derivative is prepared by polymerization of 1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylic acid, 2,2-bis(bromomethyl)-1,3-propylene glycol, diacetone acrylamide, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 2-hydroxyethyl acrylate, ethylene glycol dimethyl ether, propylene glycol n-butyl ether and 18-crown ether-6 under the action of a catalyst. The polymerization reaction method preferably includes the following steps: S1: 2,2-bis(bromomethyl)-1,3-propylene glycol and diacetone acrylamide are stirred evenly at a temperature of 25°C to 50°C, 1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylic acid and catalyst I are added, and the mixture is stirred and reacted at 30°C to 60°C for 3h to 4h to obtain a first intermediate product; S2: the first intermediate product, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 18-crown ether-6 and catalyst II are stirred and reacted at a temperature of 40°C to 70°C for 18h to 24h to obtain a second intermediate product; S3: the second intermediate product, ethylene glycol dimethyl ether, propylene glycol n-butyl ether, 2-hydroxyethyl acrylate and catalyst III are stirred and reacted at a temperature of 40°C to 90°C for 18h to 28h, and after the reaction is completed, the mixture is cooled to room temperature to obtain a viscosity reducer. The viscosity reducer prepared by the above method has both hydrophobic and hydrophilic groups, has high dispersibility, and the electrostatic force acting on cement particles is three-dimensional. A large number of small continuous stable closed spherical beneficial bubbles can be introduced into the concrete system under the premise of ensuring the strength of the concrete. Since the water is evenly distributed on the surface of a large number of bubbles, the amount of water that can move freely is reduced, the water bleeding and viscosity of the concrete are reduced, and the workability of the concrete is improved. The catalyst I, catalyst II and catalyst III can be the same or different, and are preferably independently selected from at least one of concentrated hydrochloric acid, concentrated sulfuric acid and concentrated nitric acid. The amount of the catalyst I preferably accounts for 0.1% to 1.5% of the total mass of 2,2-bis(bromomethyl)-1,3-propylene glycol, diacetone acrylamide and 1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylic acid, such as 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5% or any value therebetween. The amount of the catalyst II is preferably 0.1% to 3.0% of the total mass of 2,4,7,9-tetramethyl-5-decyne-4,7-diol and 18-crown ether-6, such as 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or any value therebetween. The amount of the catalyst III is preferably 0.1% to 4.0% of the total mass of ethylene glycol dimethyl ether, propylene glycol n-butyl ether and 2-hydroxyethyl acrylate, such as 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or any value therebetween.The molar ratio of 1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylic acid, 2,2-bis(bromomethyl)-1,3-propanediol, diacetone acrylamide, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 2-hydroxyethyl acrylate, ethylene glycol dimethyl ether, propylene glycol n-butyl ether and 18-crown ether-6 is preferably 1:(1-4):(1-6):(1-4.5):(1-4):(1-3):(1-7):(1-3.5). Based on the usage of 1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylic acid as 1 mol, the usage of the 2,2-bis(bromomethyl)-1,3-propanediol is preferably 1 to 4 mol, such as 1, 1.5, 2, 2.5, 3, 3.5, 4 mol or any value therebetween; the usage of the diacetone acrylamide is 1 to 6 mol, such as 1, 2, 3, 4, 5, 6 mol or any value therebetween; the usage of the 2,4,7,9-tetramethyl-5-decyne-4,7-diol is 1 to 4.5 mol, such as 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 mol or any value therebetween; the amount of the 2-hydroxyethyl acrylate is 1-4 mol, such as 1, 2, 3, 4 mol or any value therebetween; the amount of the ethylene glycol dimethyl ether is 1-3 mol, such as 1, 1.5, 2, 2.5, 3 mol or any value therebetween; the amount of the propylene glycol n-butyl ether is 1-7 mol, such as 1, 2, 3, 4, 5, 6, 7 mol or any value therebetween; the amount of the 18-crown ether-6 is 1-3.5 mol, such as 1, 1.5, 2, 2.5, 3, 3.5 mol or any value therebetween.

[0021] In the present invention, the main function of the air entraining agent is to significantly reduce the surface tension and interfacial energy of water, so that a large number of tiny, ball-like closed spherical bubbles (mostly with a diameter of less than 200 μm) are generated in the concrete during the mixing process, reducing the friction resistance between aggregate particles. At the same time, its molecules can be directional adsorbed on the surface of the bubbles to form a relatively firm liquid film, making the bubbles stable and not easy to break, and keeping the initial expansion of the self-compacting concrete unchanged while reducing the unit water consumption. In addition, since the water is evenly distributed on the surface of a large number of bubbles, the amount of water that can move freely is reduced, thereby reducing the water exudation of the concrete and improving water retention and cohesion. The air entraining agent is preferably at least one of sodium lauryl alcohol polyoxyethylene ether sulfate, sodium dodecyl sulfonate and triterpenoid saponin.

[0022] In the present invention, the main function of the stabilizer is that the hydroxyl groups on the stabilizer molecules and the oxygen atoms on the ether bonds form hydrogen bonds with water molecules, and the mutual diffusion between water molecules and stabilizer molecular chains allows water molecules to enter the interior of the stabilizer macromolecular chain and be subject to strong constraints, so that free water becomes bound water, thereby improving the water retention of concrete; on the other hand, the modifier improves the rheological properties of the fresh cement paste, and the porous network structure, osmotic pressure and film-forming properties of the stabilizer also hinder the diffusion of water, thereby improving the stability of concrete to heat, salt and acid and alkali. The stabilizer is selected from at least one of sodium benzoate, Wenlun glue, benzyl cyanoethyl cellulose, polyethylene glycol and carboxymethyl hydroxyethyl cellulose.

[0023] In the present invention, the main function of the preservative is to inhibit the growth of microorganisms caused by the presence of organic matter during the storage of the liquid material, and to interfere with the survival and reproduction of the microorganisms by coagulating and denaturing the proteins in the microorganisms, thereby extending the shelf life of the liquid material. The preservative is preferably calcium benzoate.

[0024] In the present invention, the particle size of the glass powder is preferably 180 mesh to 220 mesh, such as 180 mesh, 185 mesh, 190 mesh, 195 mesh, 200 mesh, 205 mesh, 210 mesh, 215 mesh, 220 mesh or any value therebetween. The particle size of the glass sand is preferably 70 mesh to 140 mesh, such as 70 mesh, 80 mesh, 90 mesh, 100 mesh, 110 mesh, 120 mesh, 130 mesh, 140 mesh or any value therebetween.

[0025] In the present invention, the cement contains both ordinary Portland cement and sulphoaluminate / aluminate cement. The mass ratio of the ordinary Portland cement to sulphoaluminate / aluminate cement is preferably 1:(0.125-8), such as 1:0.125, 1:0.2, 1:0.5, 1:1, 1:2, 1:4, 1:6, 1:8 or any value therebetween.

[0026] In the present invention, the expansion agent may be at least one of aluminum sulfate, aluminum oxide, and potassium aluminum sulfate.

[0027] In the present invention, the fumed nano-silica toughened high-strength micropowder is prepared according to the following method: halosilanes are subjected to gas phase hydrolysis reaction with hydrogen and oxygen-containing gas at high temperature, and then the generated fumed silica microparticles are quenched to aggregate into large fumed silica particles, and then the large fumed silica particles are deacidified and dried, filtered and ground, and the deacidified fumed silica obtained is mixed with silicon micropowder to obtain fumed nano-silica toughened high-strength micropowder. The specific reaction process is as follows: SiCl4+2H2+O2→SiO2+4HCl. The conditions of the gas phase hydrolysis reaction include a temperature of 1600°C to 2000°C, such as 1600°C, 1700°C, 1800°C, 1900°C, 2000°C or any value therebetween. The deacidification treatment method can be purging with nitrogen-containing air until the pH value is 4 to 6. The mass ratio of the deacidified fumed silica to the silicon micropowder can be (1 to 10): (1 to 10).

[0028] In a preferred embodiment, the modified sulfonated phenolic resin is prepared according to the following method: phenol and formaldehyde are subjected to polycondensation reaction in the presence of an alkali metal hydroxide salt, the obtained polycondensation reaction product and sodium p-aminobenzenesulfonate are dissolved in bisulfite for modification reaction, and after the modification reaction is completed, silicic acid is added to continue the high temperature reaction, and water is added during the high temperature reaction, and the obtained high temperature reaction product is the modified sulfonated phenolic resin. Wherein, the conditions of the polycondensation reaction preferably include a temperature of 50°C to 70°C, such as 50°C, 55°C, 60°C, 65°C, 70°C or any value therebetween; a time of 20min to 60min, such as 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, 60min or any value therebetween. The conditions of the modification reaction preferably include a temperature of 80°C to 120°C, such as 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C or any value therebetween; a time of 1h to 3h, such as 1h, 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h, 2.8h, 3h or any value therebetween. The conditions of the high temperature reaction preferably include a temperature of 80°C to 120°C, such as 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C or any value therebetween; a time of 2h to 5h, such as 2h, 3h, 4h, 5h or any value therebetween; preferably, water is added every 50min to 70min, and the total number of water additions is 2 to 4 times. The alkali metal hydroxide salt may be potassium hydroxide and / or sodium bisulfite.

[0029] In a preferred embodiment, the viscosity modifier contains 1 to 10 parts by weight of fused mullite, 5 to 25 parts by weight of plate-shaped corundum, 10 to 25 parts by weight of bentonite, 3 to 10 parts by weight of ceramic micropowder, 10 to 30 parts by weight of sodium nitre, 10 to 50 parts by weight of diatomaceous earth, 3 to 10 parts by weight of magadiite, 1 to 15 parts by weight of gum arabic, 1 to 5 parts by weight of polyvinyl alcohol, 1 to 8 parts by weight of sodium polyacrylate, 1 to 10 parts by weight of propylene glycol alginate and 3 to 20 parts by weight of silica fume. The particle size of the viscosity modifier is preferably 150 mesh to 250 mesh.

[0030] The preparation method of the self-compacting concrete with a slab opening provided by the invention comprises the steps of evenly mixing components of a liquid material to obtain a liquid material; and evenly mixing components of a dry material to obtain a dry material.

[0031] In addition, the present invention also provides the application of the self-compacting concrete in the field of construction.

[0032] The present invention will be described in detail below through examples.

[0033] In the following examples and comparative examples, the water reducer is a short main chain and long side chain polycarboxylic acid grafted multipolymer, purchased from Fujian Kezhijie New Materials Group Co., Ltd., with the brand name Point-MS4404; the collapse retaining agent is a long main chain and short side chain polycarboxylic acid grafted multipolymer, purchased from Fujian Kezhijie New Materials Group Co., Ltd., with the brand name Point-TS4404; sodium lauryl polyoxyethylene ether sulfate was purchased from Guangzhou Jiali Chemical Co., Ltd. with the brand name AEO-9; polyether modified silicone oil was purchased from Guangdong Nanhui New Materials Co., Ltd. with the brand name CI-735; the expansion agent is a mixture of various expansion sources such as aluminum sulfate, alumina, and potassium aluminum sulfate, purchased from Jiangsu Dejiatuoda Building Materials Co., Ltd. with the brand name UEA; polyethylene glycol was purchased from Guangzhou Zhongye Chemical Co., Ltd. with the brand name PEG-600.

[0034] Preparation Example 1 Beautifying agent and preparation method thereof

[0035] Polyoxyethylene sorbitan monooleate (purchased from Chemical Book, CAS No. 9005-65-6), dodecanol, dodecenyl succinic anhydride, concentrated sulfuric acid and triethylamine were added into a reactor in a mass ratio of 100:30:20:5:8, the pH value was adjusted to 4, the temperature was controlled at 60°C and the reaction was carried out for 7 hours. After the reaction was completed, the unreacted raw materials were removed by rotary evaporation to obtain dodecanol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer.

[0036] Preparation Example 2 Viscosity reducer and preparation method thereof

[0037] S1: Add 1500 g of 2,2-bis(bromomethyl)-1,3-propylene glycol and 800 g of diacetone acrylamide into a four-necked flask, control the temperature at 35°C and stir the materials evenly, add 1200 g of 1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylic acid, and then add 10 mL of concentrated sulfuric acid, stir and react at 45°C for 3.5 hours to obtain a first intermediate product;

[0038] S2: Add 860 g of 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 950 g of 18-crown ether-6 and 20 mL of concentrated sulfuric acid to the first intermediate product obtained in S1, and stir and react at 50° C. for 20 h to obtain a second intermediate product;

[0039] S3: Add 1275 g of ethylene glycol dimethyl ether, 1760 g of propylene glycol n-butyl ether, 900 g of 2-hydroxyethyl acrylate and 30 mL of catalyst to the second intermediate product obtained in S2, stir the reaction at 70°C for 24 hours, and cool to room temperature to obtain an alcohol-ester-ether-phosphoric acid-amide multi-copolymer derivative.

[0040] Preparation Example 3 Polymer emulsion and preparation method thereof

[0041] 75g of composite emulsifier was added to 25mL of deionized water and stirred to dissolve, and then 50g of mixed monomers of butyl acrylate, styrene and acrylic acid in a molar ratio of 1:5:5 was added and vigorously stirred for 30 minutes to prepare a pre-emulsion. Potassium persulfate was dissolved in an appropriate amount of water to prepare an initiator solution with a concentration of 5wt%. In a 250mL four-necked flask equipped with a reflux condenser, an electric stirrer, a constant pressure dropping funnel and a thermometer, add an appropriate amount of 15g sodium bicarbonate, 60mL deionized water and 25g composite emulsifier, stir and dissolve, heat to 60°C, add 20mL initiator solution, drop 40mL pre-emulsion within 30min, and keep warm at 75°C until the liquid turns blue; mix 2mol vinyl triethoxysilane into 160mL pre-emulsion, drop 160mL pre-emulsion and 30mL initiator solution into the flask within 2.5h, keep warm for 1.5h after dropping, cool to below 40°C, adjust the pH value to 7.5 with ammonia water, filter and store, and obtain a polymer emulsion, that is, a ternary copolymer emulsion of silicone-styrene-acrylate. Among them, the composite emulsifier is a mixture of nonylphenol polyoxyethylene ether and sodium dodecyl sulfate in a mass ratio of 3:1.

[0042] Preparation Example 4 Modified sulfonated phenolic resin and preparation method thereof

[0043] 1 mol of phenol, 1 mol of formaldehyde and 0.3 mol of potassium hydroxide are reacted at 60±5°C for 40 minutes, 20 g of sodium bisulfite is added to the obtained reaction product and stirred to dissolve, 50 g of sodium p-aminobenzenesulfonate is added at the same time after dissolution, and then the reaction temperature is raised to 100°C and kept constant for 2 hours, 50 g of silicic acid is added to the obtained product and the reaction is continued at 100°C for 6 hours, and water is added every 60 minutes to obtain a modified sulfonated phenolic resin.

[0044] Preparation Example 5 Viscosity modifier and preparation method thereof

[0045] 5 parts of fused mullite, 10 parts of plate-like corundum, 15 parts of bentonite, 8 parts of ceramic micropowder, 15 parts of sodium nitre, 22 parts of diatomaceous earth, 8 parts of magadiite, 8 parts of gum arabic, 3 parts of polyvinyl alcohol (number average molecular weight is 2000), 6 parts of sodium polyacrylate (number average molecular weight is 3000), 8 parts of propylene glycol alginate (purchased from Green Union (Jining) Chemical Technology Co., Ltd., CAS No. 2546-56-2), and 15 parts of silica fume are mixed evenly and ground to a particle size D90 of 200 mesh to obtain a viscosity modifier.

[0046] Preparation Example 6 Fumed nano-silicon dioxide toughened high-strength micropowder and its preparation method

[0047] 100g of silicon tetrachloride, 25g of silicon tetrafluoride and 15g of methyl silicon trichloride were hydrolyzed in a mixed atmosphere of hydrogen and oxygen at a volume ratio of 3:1 at 1800°C for 8h to generate fumed silica microparticles. The high-temperature fumed silica microparticles were cooled to 500°C at a rate of 10°C / s to aggregate small particles into large particles, and the product was collected by a cyclone separator. The collected large fumed silica particles were sent to a deacidification furnace and purged with nitrogen-containing air to a pH value of 5 to remove residual acidic substances. The product was then ground to a particle size of 10 microns D90 and mixed with silicon micropowder with a particle size of 10 microns D90 at a mass ratio of 7:3 to obtain fumed nano-silica toughened high-strength micropowder.

[0048] Example 1: Self-compacting concrete and its preparation method

[0049] The liquid and dry materials of the self-compacting concrete for lifting slabs were prepared in the following proportions. The liquid material consisted of 180 kg of water reducing agent, 40 kg of slump retaining agent, 20 kg of citric acid, 30 kg of potassium formate, 5 kg of sodium lauryl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 6 kg of Wenlun glue, 10 kg of calcium benzoate, 30 kg of lauryl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multi-polymer, 30 kg of alcohol-ester-ether-phosphoric acid-amide multi-polymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 627 kg of water. The dry material consists of 250kg of ordinary Portland cement, 150kg of aluminate cement, 50kg of gypsum, 50kg of 180-220 mesh glass powder, 50kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 50kg of modified sulfonated phenolic resin, 650kg of 70-140 mesh glass sand, 850kg of 5mm-16mm crushed stone, and 30kg of viscosity modifier.

[0050] Example 2: Self-compacting concrete and its preparation method

[0051] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 180 kg of water reducing agent, 50 kg of slump retaining agent, 25 kg of sodium gluconate, 15 kg of calcium nitrate, 10 kg of triisopropanolamine, 4 kg of sodium dodecyl sulfonate, 2 kg of polyether-modified silicone oil, 3 kg of benzyl cyanoethyl cellulose, 10 kg of calcium benzoate, 30 kg of dodecanol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multi-polymer, 35 kg of alcohol-ester-ether-phosphoric acid-amide multi-polymer derivative, 15 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 621 kg of water. The dry material consists of 275kg of ordinary Portland cement, 125kg of aluminate cement, 50kg of gypsum, 70kg of 180-220 mesh glass powder, 35kg of expansion agent, 90kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 45kg of modified sulfonated phenolic resin, 670kg of 70-140 mesh glass sand, 840kg of 5-16mm crushed stone, and 30kg of viscosity modifier.

[0052] Example 3: Self-compacting concrete and its preparation method

[0053] The liquid and dry materials of the self-compacting concrete for lifting slabs were prepared in the following proportions. The liquid material consisted of 170 kg of water reducing agent, 60 kg of slump retaining agent, 30 kg of sodium hexametaphosphate, 20 kg of sodium fluoride, 2 kg of sodium dodecyl sulfonate, 3 kg of triterpenoid saponin, 2 kg of polyether modified silicone oil, 8 kg of sodium benzoate, 10 kg of calcium benzoate, 25 kg of dodecanol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multi-polymer, 30 kg of alcohol-ester-ether-phosphoric acid-amide multi-polymer derivative, 25 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 615 kg of water. The dry material consists of 290kg of ordinary Portland cement, 110kg of aluminate cement, 60kg of gypsum, 90kg of 180-220 mesh glass powder, 25kg of expansion agent, 80kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 40kg of modified sulfonated phenolic resin, 640kg of 70-140 mesh glass sand, 855kg of 5-16mm crushed stone, and 40kg of viscosity modifier.

[0054] Example 4: Self-compacting concrete and its preparation method

[0055] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 609 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0056] Example 5: Self-compacting concrete and its preparation method

[0057] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 80 kg of slump retaining agent, 15 kg of citric acid, 20 kg of sodium gluconate, 15 kg of calcium nitrate, 7 kg of triterpenoid saponin, 2 kg of polyether modified silicone oil, 5 kg of carboxymethyl hydroxyethyl cellulose, 10 kg of calcium benzoate, 30 kg of dodecanol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multi-polymer, 40 kg of alcohol-ester-ether-phosphoric acid-amide multi-polymer derivative, 30 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 576 kg of water. The dry material consists of 320kg of ordinary Portland cement, 80kg of sulphoaluminate cement, 70kg of gypsum, 110kg of 180-220 mesh glass powder, 30kg of expansion agent, 80kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 30kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 845kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0058] Example 6: Self-compacting concrete and its preparation method

[0059] The liquid and dry materials of the self-compacting concrete for lifting slabs were prepared in the following proportions. The liquid material consisted of 170 kg of water reducing agent, 90 kg of slump retaining agent, 25 kg of sodium hexametaphosphate, 20 kg of sodium gluconate, 10 kg of potassium formate, 6 kg of triterpenoid saponin, 1 kg of polyether modified silicone oil, 6 kg of Wenlun glue, 10 kg of calcium benzoate, 40 kg of dodecanol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 30 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 572 kg of water. The dry material consists of 330kg of ordinary Portland cement, 50kg of sulphoaluminate cement, 80kg of gypsum, 125kg of 180-220 mesh glass powder, 30kg of expansion agent, 70kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 30kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 850kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0060] Comparative Example 1 (beautifying agent exceeds the lower limit)

[0061] Liquid and dry materials were prepared according to the method of Example 4, except that the amount of dodecanol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer was adjusted to 5 kg and the amount of water was adjusted to 634 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0062] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 5 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer, and 634 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0063] Comparative Example 2 (beautifying agent exceeds the upper limit)

[0064] Liquid and dry materials were prepared according to the method of Example 4, except that the amount of dodecanol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer was adjusted to 130 kg and the amount of water was adjusted to 509 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0065] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 130 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer latex, and 509 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0066] Comparative Example 3 (Viscosity reducer exceeds the lower limit)

[0067] Liquid and dry materials were prepared according to the method of Example 4, except that the amount of alcohol-ester-ether-phosphoric acid-amide multi-copolymer derivative was adjusted to 5 kg and the amount of water was adjusted to 629 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0068] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 5 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer, and 629 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0069] Comparative Example 4 (Viscosity reducer exceeds upper limit)

[0070] Liquid and dry materials were prepared according to the method of Example 4, except that the amount of alcohol-ester-ether-phosphoric acid-amide multi-copolymer derivative was adjusted to 125 kg and the amount of water was adjusted to 509 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0071] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 125 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer, and 509 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0072] Comparative Example 5 (Glass powder exceeds the lower limit)

[0073] The liquid material and the dry material were prepared according to the method of Example 4, except that the amount of glass powder was adjusted to 5 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0074] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 609 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 5kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0075] Comparative Example 6 (Glass powder exceeds the upper limit)

[0076] The liquid material and the dry material were prepared according to the method of Example 4, except that the amount of glass powder was adjusted to 170 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0077] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 609 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 170kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0078] Comparative Example 7 (glass sand exceeds the lower limit)

[0079] Liquid and dry materials were prepared according to the method of Example 4, except that the amount of glass sand was adjusted to 480 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0080] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 609 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 480kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0081] Comparative Example 8 (glass sand exceeds upper limit)

[0082] Liquid and dry materials were prepared according to the method of Example 4, except that the amount of glass sand was adjusted to 830 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0083] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 609 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 830kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0084] Comparative Example 9 (Fumed Silica Powder Exceeds Lower Limit)

[0085] The liquid material and the dry material were prepared according to the method of Example 4, except that the amount of the fumed nano-silicon dioxide toughened high-strength micropowder was adjusted to 30 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0086] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 609 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 30kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0087] Comparative Example 10 (Fumed Silica Powder Exceeds Upper Limit)

[0088] The liquid material and the dry material were prepared according to the method of Example 4, except that the amount of the fumed nano-silicon dioxide toughened high-strength micropowder was adjusted to 210 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0089] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 609 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 210kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0090] Comparative Example 11 (phenolic resin exceeds the lower limit)

[0091] The liquid material and the dry material were prepared according to the method of Example 4, except that in the process of preparing the dry material, the amount of the liquid material modified sulfonated phenolic resin was adjusted to 5 kg, that is, exceeding the lower limit, and the other conditions were the same as those of Example 4. The specific process is as follows:

[0092] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 609 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 5kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0093] Comparative Example 12 (phenolic resin exceeds upper limit)

[0094] The liquid material and the dry material were prepared according to the method of Example 4, except that, in the process of preparing the dry material, the amount of the liquid material modified sulfonated phenolic resin was adjusted to 85 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0095] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 609 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 85kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0096] Comparative Example 13 (viscosity modifier exceeds the lower limit)

[0097] The liquid material and the dry material were prepared according to the method of Example 4, except that in the process of preparing the dry material, the amount of the viscosity modifier was adjusted to 5 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0098] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 609 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 5kg of viscosity modifier.

[0099] Comparative Example 14 (viscosity modifier exceeds upper limit)

[0100] The liquid material and the dry material were prepared according to the method of Example 4, except that in the process of preparing the dry material, the amount of the viscosity modifier was adjusted to 105 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0101] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 20 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 609 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 105kg of viscosity modifier.

[0102] Comparative Example 15 (emulsion exceeds the lower limit)

[0103] The liquid material and the dry material were prepared according to the method of Example 4, except that, during the preparation of the liquid material, the amount of the polymer emulsion was adjusted to 5 kg and the amount of water was adjusted to 624 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0104] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multipolymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multipolymer derivative, 5 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 624 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0105] Comparative Example 16 (emulsion exceeds upper limit)

[0106] The liquid material and the dry material were prepared according to the method of Example 4, except that, during the preparation of the liquid material, the amount of the polymer emulsion was adjusted to 120 kg and the amount of water was adjusted to 509 kg, that is, exceeding the lower limit. The other conditions were the same as those of Example 4. The specific process was as follows:

[0107] The liquid and dry materials of the self-compacting concrete for the slab are prepared in the following proportions. The liquid material is composed of 170 kg of water reducing agent, 70 kg of slump retaining agent, 10 kg of maltodextrin, 20 kg of sodium gluconate, 20 kg of triisopropanolamine, 6 kg of sodium dodecyl polyoxyethylene ether sulfate, 2 kg of polyether modified silicone oil, 8 kg of polyethylene glycol, 10 kg of calcium benzoate, 30 kg of dodecyl alcohol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multi-polymer, 25 kg of alcohol-ester-ether-phosphoric acid-amide multi-polymer derivative, 120 kg of organosilicon-styrene-acrylate ternary copolymer emulsion, and 509 kg of water. The dry material consists of 305kg of ordinary Portland cement, 95kg of sulphoaluminate cement, 65kg of gypsum, 100kg of 180-220 mesh glass powder, 35kg of expansion agent, 100kg of 200 mesh fumed nano-silica toughened high-strength micropowder, 35kg of modified sulfonated phenolic resin, 630kg of 70-140 mesh glass sand, 830kg of 5-16mm crushed stone, and 35kg of viscosity modifier.

[0108] Comparative Example 17 (without adding coagulant)

[0109] The self-compacting concrete was prepared according to the method of Example 1, except that the setting regulator was replaced by the same weight portion of the defoamer, and the other conditions were the same as in Example 1 to obtain the liquid and dry materials of the self-compacting concrete.

[0110] Comparative Example 18 (without adding defoamer)

[0111] The self-compacting concrete was prepared according to the method of Example 1, except that the defoamer was replaced by the same weight of the setting regulator. The other conditions were the same as those of Example 1, and the liquid and dry materials of the self-compacting concrete were obtained.

[0112] Comparative Example 19 (without addition of polymer emulsion)

[0113] The self-compacting concrete was prepared according to the method of Example 1, except that the polymer emulsion was replaced by the same weight of the setting regulator. The other conditions were the same as those of Example 1, and the liquid and dry materials of the self-compacting concrete were obtained.

[0114] Test Case

[0115] 15kg of liquid material, 2400kg of dry material and 225kg of water were mixed and stirred at 30°C and uniformly formed, and then moisturizing and curing were carried out according to the age, thereby obtaining C40 peel-off board self-compacting concrete products. The results of testing its performance are shown in Appendix 1.

[0116]

[0117]

[0118] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A self-compacting concrete with a slab opening, characterized in that: The self-compacting concrete comprises liquid material and dry material; the liquid material contains 170-180 parts by weight of water reducing agent, 40-90 parts by weight of slump retaining agent, 40-60 parts by weight of setting regulator, 0.1-2 parts by weight of defoamer, 10-30 parts by weight of polymer emulsion, 10-40 parts by weight of beautifier, 20-40 parts by weight of viscosity reducer and 500-650 parts by weight of water and 0-10 parts by weight of air entraining agent, 0-10 parts by weight of stabilizer and 0-10 parts by weight of preservative, and the setting regulator is selected from calcium nitrate, triisopropanolamine, sodium fluoride, potassium fluoride, sodium formate, potassium formate, citric acid, sodium hexametaphosphate, At least one of potassium hexametaphosphate, sodium gluconate, potassium gluconate and maltodextrin, the defoamer is polyether modified silicone oil, the polymer emulsion is silicone modified styrene and acrylate copolymer emulsion; the dry material contains 50-130 weight parts of glass powder, 600-700 weight parts of glass sand, 350-400 weight parts of cement, 800-900 weight parts of crushed stone, 50-80 weight parts of gypsum, 30-50 weight parts of expansion agent, 70-100 weight parts of gas-phase nano-silica toughened high-strength micropowder, 30-50 weight parts of modified sulfonated phenolic resin and 30-40 weight parts of viscosity modifier.

2. The self-compacting concrete according to claim 1, characterized in that: The self-compacting concrete for lifting slabs also contains added water, and the mass ratio of the liquid material, the dry material and the added water is (0.3-3):(100-500):(10-20).

3. The self-compacting concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid grafted multipolymer with a short main chain and long side chains; the collapse retaining agent is a polycarboxylic acid grafted multipolymer with a long main chain and short side chains.

4. The self-compacting concrete according to claim 1, characterized in that: The organosilicon-modified styrene and acrylate copolymer emulsion is an organosilicon-styrene-acrylate ternary copolymer emulsion; Preferably, the organosilicon-styrene-acrylate ternary copolymer emulsion is prepared by emulsion polymerization of unsaturated organosilicon monomers, styrene monomers and acrylic acid / ester monomers; Preferably, the emulsion polymerization reaction method includes dissolving the composite emulsifier I, acrylic acid / ester monomers and styrene monomers in water to obtain a pre-emulsion; dissolving the initiator in water to obtain an initiator solution; dissolving bicarbonate and composite emulsifier II in water and heating to 50°C to 70°C, adding part of the pre-emulsion and part of the initiator solution, and then heating to 75°C to 80°C to keep the temperature until the liquid turns blue; dissolving the unsaturated silicone monomer in the remaining pre-emulsion, dripping the remaining initiator solution, keeping the temperature after dripping, and cooling to below 40°C after the reaction is completed, adjusting the pH value to 7 to 8, and filtering to obtain a silicone-styrene-acrylate ternary copolymer emulsion.

5. The self-compacting concrete according to claim 1, characterized in that: The beautifying agent is a grafted multi-polymer of dodecanol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride; Preferably, the beautifying agent is prepared according to the following method: polyoxyethylene sorbitan monooleate, dodecanol, and dodecenyl succinic anhydride are subjected to graft copolymerization reaction under the action of concentrated sulfuric acid and organic amine to obtain dodecanol-polyoxyethylene sorbitan monooleate-dodecenyl succinic anhydride grafted multi-polymer; Preferably, the mass ratio of polyoxyethylene sorbitan monooleate, dodecanol, dodecenyl succinic anhydride, concentrated sulfuric acid and organic amine is 100:(15-50):(3-30):(1-10):(3-15); Preferably, the graft copolymerization reaction conditions include a temperature of 50° C. to 90° C., a pH value of 2 to 6, and a reaction time of 6 to 8 hours.

6. The self-compacting concrete according to claim 1, characterized in that: The viscosity reducer is an alcohol-ester-ether-phosphoric acid-amide multi-polymer derivative; Preferably, the alcohol-ester-ether-phosphoric acid-amide multi-copolymer derivative is prepared by polymerizing 1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylic acid, 2,2-bis(bromomethyl)-1,3-propylene glycol, diacetone acrylamide, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 2-hydroxyethyl acrylate, ethylene glycol dimethyl ether, propylene glycol n-butyl ether and 18-crown ether-6 under the action of a catalyst; Preferably, the polymerization reaction method comprises the following steps: S1: 2,2-bis(bromomethyl)-1,3-propylene glycol and diacetone acrylamide are stirred uniformly at a temperature of 25°C to 50°C, 1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylic acid and catalyst I are added, and the mixture is stirred and reacted at 30°C to 60°C for 3h to 4h to obtain a first intermediate product; S2: stirring the first intermediate product, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 18-crown ether-6 and catalyst II at a temperature of 40° C. to 70° C. for 18 h to 24 h to obtain a second intermediate product; S3: Stir the second intermediate product, ethylene glycol dimethyl ether, propylene glycol n-butyl ether, 2-hydroxyethyl acrylate and catalyst III at a temperature of 40°C to 90°C for 18h to 28h, and after the reaction is completed, cool to room temperature to obtain a viscosity reducer.

7. The self-compacting concrete according to claim 1, characterized in that: The air entraining agent is selected from at least one of sodium lauryl polyoxyethylene ether sulfate, sodium dodecyl sulfonate and triterpenoid saponin; the stabilizer is selected from at least one of sodium benzoate, Wenlun gum, benzyl cyanoethyl cellulose, polyethylene glycol and carboxymethyl hydroxyethyl cellulose; and the preservative is calcium benzoate.

8. The self-compacting concrete according to claim 1, characterized in that: The particle size of the glass powder is 180-220 mesh, and the particle size of the glass sand is 70-140 mesh; Preferably, the cement contains both ordinary Portland cement and sulphoaluminate / aluminate cement; Preferably, the mass ratio of ordinary Portland cement to sulphoaluminate / aluminate cement is 1:(0.125-8); Preferably, the fumed nano-silica toughened high-strength micropowder is prepared by the following method: a halogenated silane is subjected to a gas-phase hydrolysis reaction with hydrogen and an oxygen-containing gas at a high temperature, the generated fumed silica microparticles are quenched to aggregate into large fumed silica particles, the large fumed silica particles are then deacidified, dried, filtered and ground, and the deacidified fumed silica obtained is mixed with silicon micropowder to obtain the fumed nano-silica toughened high-strength micropowder; Preferably, the modified sulfonated phenolic resin is prepared according to the following method: phenol and formaldehyde are subjected to a polycondensation reaction in the presence of an alkali metal hydroxide salt, the obtained polycondensation reaction product and sodium p-aminobenzenesulfonate are dissolved in a bisulfite for a modification reaction, and after the modification reaction is completed, silicic acid is added to continue the high-temperature reaction, and water is added during the high-temperature reaction. The obtained high-temperature reaction product is the modified sulfonated phenolic resin; preferably, the conditions of the polycondensation reaction include a temperature of 50°C to 70°C and a time of 20min to 60min; preferably, the conditions of the modification reaction include a temperature of 80°C to 120°C and a time of 1h to 3h; preferably, the conditions of the high-temperature reaction include a temperature of 80°C to 120°C and a time of 2h to 5h, water is added every 50min to 70min, and the total number of water additions is 2 to 4 times; preferably, the alkali metal hydroxide salt is potassium hydroxide and / or sodium bisulfite; Preferably, the viscosity modifier contains 1 to 10 parts by weight of fused mullite, 5 to 25 parts by weight of plate-like corundum, 10 to 25 parts by weight of bentonite, 3 to 10 parts by weight of ceramic micropowder, 10 to 30 parts by weight of sodium nitre, 10 to 50 parts by weight of diatomaceous earth, 3 to 10 parts by weight of magadiite, 1 to 15 parts by weight of gum arabic, 1 to 5 parts by weight of polyvinyl alcohol, 1 to 8 parts by weight of sodium polyacrylate, 1 to 10 parts by weight of propylene glycol alginate and 3 to 20 parts by weight of silica fume.

9. The method for preparing the self-compacting concrete according to any one of claims 1 to 8, characterized in that: The method comprises mixing various components of liquid material evenly to obtain liquid material; and mixing various components of dry material evenly to obtain dry material.

10. Use of the self-compacting concrete according to any one of claims 1 to 9 in the field of construction.

Citation Information

Patent Citations

  • Method for preparing modified sulfonated phenolic resin for drilling fluids

    CN102911329A

  • Preparation method of viscosity-reducing type polycarboxylate water reducer

    CN109053974A

  • Pumping prestressed concrete pipe pile and preparation method thereof

    CN117486564A

  • Method for adjusting curing time of room-temperature curable epoxy resin composition and method for reinforcing concrete structure

    JP2003201337A

  • Composition of tunnel lining concrete and production method thereof

    JP2015218074A

Cited By

  • Self-curing concrete and preparation method thereof

    CN120172692A